Identifikasi risiko ergonomi dengan metode Nordic Body Map (NBM) pada pekerja pembuatan tahu di kelurahan Abian Tubuh Kota Mataram - Suwati Suwati; Muanah Muanah; Basirun Basirun; Ahmad Akromul Huda; Ida Wahyuni (Universitas Muhammadiyah Mataram, 2023)
Humans as workers play an important role in producing tofu products in quality and quantity. Making production room facilities needs good arrangement so that workers do not feel risks or complaints while carrying out activities. The purpose of this research was to help the level of complaints felt by workers in the production of tofu using the Nordic Body Map (NBM) method. The method used in this study was a descriptive method by exploring problems using a questionnaire to get 4 categories of complaint levels, namely not sick, slightly sick, sick, and very sick. There were 8 subjects studied consisting of 4 male workers and 4 female workers with a minimum working period of 5 years. The results and discussion show that the work station for making tofu needs rearrangement to facilitate moving from one station to the next work station, and found complaints felt by workers with a total score in the range of 63% -88% (high risk) in the upper neck , left and right shoulder, right wrist, right upper arm, waist, left and right ankle and left and right leg so that a comprehensive action is needed to be corrected immediately